HISTORY OF THE DEVELOPMENT OF SECONDARY RESIDENTIAL HOUSES IN THE CONSTRUCTION OF CITIES OF UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2023)
The history of the development of medium-sized residential houses in the construction of cities in Uzbekistan is a fascinating journey that reflects the evolving urban landscape of the country. Over the years, the architectural style and construction methods have been influenced by various factors, including culture, technology, and social changes. This article aims to shed light on this historical process and provide insights into the evolution of medium-sized residential houses in Uzbekistan.